Desmopressin acetate the first sublingual tablet to treat nocturia due to nocturnal polyuria. Issue 8 (3rd August 2021) - Alford, Natasha; Hashim, Hashim
ABSTRACT: Introduction : Desmopressin was widely used to treat nocturnal polyuria in adults under the age of 65 due to the well-established risk of hyponatremia. Since the prevalence of nocturia increases with age, and with an aging population, those most affected were excluded from treatment. Recently, a new lower dose sublingual tablet formulation that optimizes the balance between efficacy and tolerability has been licensed for symptomatic treatment of nocturia due to idiopathic nocturnal polyuria in adults of any age, with the caveat of regular serum monitoring for those over 65. This newer formulation aims to achieve the same clinical outcomes as previous formulations while reducing the risk of hyponatremia. Areas covered : This review will look at the pharmacology of the newly formulated desmopressin and examine the results of the clinical trials that would support its treatment of adult nocturia with idiopathic nocturnal polyuria. Expert opinion : When reporting on the clinical efficacy of desmopressin on nocturia, it is important for clinical trials to publish their complete data on nocturnal and 24-hour urine voided volumes. Further research examining the physiological reasoning behind this gender-specific dosing for desmopressin and the optimal recommended treatment duration of desmopressin for those over 65 is needed.